Enhancement of Ethylene-Butene Terpolymer Performance via Carbon Nanotube-Induced Nanodispersion of Montmorillonite Layers - Li Zhang; Jianming Liu; Duanjiao Li; Wenxing Sun; Zhi Li; Yongchao Liang; Qiang Fu; Nian Tang; Bo Zhang; Fei Huang; Xuelian Fan; Yuansi Wei; et al. (Crystals, 2025)
In this study, the enhancement mechanism of the nano-dispersion of stearic acid-modified montmorillonite (SMMT) induced by carbon nanotubes (CNTs) in ethylene-butene terpolymer (EBT) was comprehensively investigated, and the regulation effect of composite fillers on EBT properties was revealed. Scanning electron microscopy (SEM) confirmed that SMMT achieved homogeneous nanoscale dispersion after CNT addition, and the size of aggregates was greatly reduced. Four-cycle strain-scanning analysis revealed a 200% increase in rubber–filler (R-F) interaction strength due to CNT incorporation. At the optimal CNT/SMMT ratio of 1:5, the EBT composites exhibited a 40.4% increase in Young’s modulus, 71.4% enhancement in tensile strength, and maintained 250% elongation at break, effectively addressing the strength–toughness trade-off of traditional rigid fillers. Thermogravimetric analysis (TGA) showed near 20 °C elevation in EBT composites’ maximum decomposition temperature, while water contact angle measurements indicated a hydrophobicity increase to 117.5° and water absorption rate below 0.2%. The quantitative improvement in thermal oxidation stability and hydrophobic barrier performance was achieved simultaneously.